Thin films of copper indium selenide fabricated with high atom economy by electrophoretic deposition of nanocrystals under flow. (2nd November 2016) - Dillon, Andrew D.; Le Quoc, Long; Goktas, Mustafa; Opasanont, Borirak; Dastidar, Subham; Mengel, Shawn; Baxter, Jason B.; Fafarman, Aaron T.
Abstract: Electrophoretic deposition (EPD) of colloidal nanocrystals (NCs) under flow is explored as a general method for the fabrication of semiconducting thin films. For photovoltaic applications, a low process voltage is highly desirable to avoid damaging the accreting semiconductor. Here we report a continuous flow reactor design that can operate at reduced voltage compared to a traditional batch reactor while preserving the electrophoretic velocity of the NCs by utilizing narrow electrode spacing. In a batch reactor, the low ratio of reactor volume to electrode surface area dictated by such a narrow spacing of the electrodes would impose a limit on the mass of nanocrystals that are resident in the reactor and therefore the thickness of the films that can be deposited. By continuously flowing the colloidal dispersion of NCs this limitation is obviated and thick films can be deposited. Through modeling and experiment we demonstrate the process parameters necessary to completely utilize the NCs in the feed solution, thereby achieving nearly 100% atom economy in the deposition process. The reactor design is compatible with large area substrates and is specifically designed to enable continuous, high-rate fabrication of the active layer of photovoltaic cells. Graphical abstract: Highlights: Novel flow reactor for electrophoretic deposition (EPD) of semiconductor nanocrystals. Reactor design criteria for making uniform thin films with 100% atom efficiency. Experimental results compared to model of electrophoresis under flow.